The impact of interventions involving electronic monitoring on young people and adults who offend - Paddock, E.L. (2019)
This thesis provides an overview of interventions using supervision and surveillance methods in managing young people who have been convicted of an offence in the community. A range of approaches including a systematic review, a single case report and an empirical quantitative study were used to explore this research area. Following a brief introduction to the thesis in chapter 1, chapter 2 critically reviews the use of electronic monitoring (EM) as a surveillance method during intensive supervision in the management of offenders in the community. Chapter 3 systematically reviews the impact of interventions including electronic monitoring for individuals who offend and assesses the quality of the existing research in this area. Of the 16 included studies, only nine (56.25%) could be considered to have shown lower recidivism rates for EM offenders that were statistically significant. Chapter 4 provides an outline of how EM is used in an intensive community programme, and describes the importance of reviewing the impact of interventions involving EM to manage young people who offend in the community. In chapter 5, a case report is used to display the range of intensive interventions used together with EM, whilst a young person is supervised on an ISS order. His history and psychometric testing informed the assessment, formulation and treatment provided by myself and the multi-agency team at the YOT. Chapter 6 presents an empirical research study which explores an Intensive Supervision and Surveillance (ISS) programme, using EM for surveillance. The findings indicate that intensive supervision programmes in the community cannot cease offending behaviour, but can contribute to reducing the severity of offences. The final chapter of the thesis provides a general discussion of the findings and implications in relation to the management of young people who offend in the community.